Tie-2 regulates endothelial morphological responses to shear stress by FOXO1-triggered autophagy - Mana Ghanbarpour Houshangi; Keisuke Shirakura; Dietmar Vestweber (PLoS ONE, 2025)
Introduction Endothelial cells respond to flow-induced shear stress by morphological changes, a process which is important for vascular development and physiology. High laminar shear stress activates Tie-2 which supports endothelial junction integrity and protects against vascular leaks and the generation of atherosclerotic plaques. Methods We have examined the role of Tie-2 and FOXO1 in controlling vascular endothelial cell morphology under physiological shear stress. To address this, we exposed human umbilical vein endothelial cells (HUVECs) transfected with siRNA to 15 dyn/cm2 of shear stress for 24 hours. The resulting cells were analyzed by immunofluorescence staining. Results We found that shear stress-induced activation of Tie-2 is required for endothelial cell alignment and elongation in the direction of flow. Mechanistically, we found that FOXO1 is an essential target downstream of Tie-2, which becomes translocated from the nucleus into the cytosol. There, FOXO1 stimulates the formation of autophagosomes, and both FOXO1 and autophagy stimulation are needed for Tie-2-dependent cell alignment. Conclusion In conclusion, laminar fluid shear stress stimulates a novel Tie-2-FOXO1-autophagy signaling axis which is required for endothelial cell alignment. This represents a new mechanism by which Tie-2 contributes to vascular protection under laminar shear stress.